Kesenjangan Implementasi Kebijakan Kesehatan Ibu dan Anak di Indonesia: Analisis Terintegrasi Berdasarkan Survei Kesehatan Indonesia 2023 - Sitti Raodhah; Nurul Asikin; Nurul Astria; Syamsul Alam (Nutrition Science and Health Research, 2026)
Despite maternal and child health (MCH) policies in Indonesia, substantial gaps persist between policy targets and service delivery outcomes. This study analyzed MCH conditions and identified factors underlying policy implementation gaps using an integrated policy analysis framework. This descriptive-interpretive policy analysis integrated published national-level indicators from the 2023 Indonesian Health Survey with a structured narrative review of scientific literature and national policy documents published between 2019 and 2025. Evidence was synthesized using four complementary frameworks: Evidence-Based Policy, Systems Thinking, Political Economy of Health, and Wicked Problem. Major discontinuities were identified across the maternal and newborn continuum of care. Although first antenatal care coverage reached 86.7%, only 17.6% of pregnant women completed six recommended visits. Complete neonatal and postpartum care coverage remained low at 40.5% and 26.8%, respectively. Maternal anemia affected 27.7% of pregnant women, while child stunting prevalence remained at 21.5%. The integrated analysis identified discontinuities in care and indicated that unequal local implementation capacity, output-oriented accountability, fragmented financing, referral-system limitations, and weak intersectoral coordination may contribute to implementation gaps. These interacting factors indicate that MCH challenges constitute a complex policy problem that cannot be addressed through isolated interventions. Improving MCH outcomes requires strengthening the continuum of care, enhancing service quality and referral systems, implementing outcome-based accountability, reinforcing intersectoral governance, and developing adaptive health- system management.